Análise estrutural de edificações de pequeno porte: estudo de caso - Pinheiro, Marco Antônio (2008)
The beams, pillars and slabs, are basic structural elements which compose the superstructure of the vast majority of buildings, including those of small size, which account for approximately 90% of them. There is a lacuna in the technical publications that address the structure of these buildings with numerical examples, analysis of the results, comments and general recommendations. The structures are differentiated according to their complexity. The modeling and analysis of a structure seeking their behavior closest to the real, even for simple structures are often complex and difficult. By the constant evolution of computer programs, each day it is getting a greater approximation of the real behavior of the structures. For the same structure it can be taken several structural models, resulting in different consumption of materials. This paper deals with the calculation of the superstructure of a two-story house usually composed by prefabricated slabs, rectangular beams and rectangular pillars which are presented through a general theoretical introduction with the main prescriptions of NBR 6118: 2003 and NBR 14859-1 (prefabricated slab requirements Part 1: unidirectional slabs) and the main recommendations of the Recommended Practice Ibracon for structures of small size. Through numerical examples with variations in the shape of the superstructure on the basis of two types of masonry adopted, this elements are calculated using the software for structural calculation, taking into account the calculation by tridimensional portico and grillage analogy. Important aspects of the structural point of view are presented. The results were analysed and compared also general comments and recommendation are presented.